2008
DOI: 10.1007/s10295-008-0447-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and immobilization of the intracellular invertase INVA, from Zymomonas mobilis on crystalline cellulose and Nylon-6

Abstract: This paper presents two immobilization methods for the intracellular invertase (INVA), from Zymomonas mobilis. In the first method, a chimeric protein containing the invertase INVA, fused through its C-terminus to CBDCex from Cellulomonas fimi was expressed in Escherichia coli strain BL21 (DE3). INVA was purified and immobilized on crystalline cellulose (Avicel) by means of affinity, in a single step. No changes were detected in optimal pH and temperature when INVA-CBD was immobilized on Avicel, where values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The increase in K m after immobilization was probably due to the mass transfer resistance to the substrate into the polymer matrix, and effect of the increasing degree of polymerization of substrate caused increase in this value (Abdel-Naby et al, 1999;Curcio et al, 2014;Kusano et al, 1989;Mazutti et al, 2007). Higher V max observed for the immobilized enzyme was rather unusual; however, such increase has been observed in case of immobilized inulinase (Calixto-Romo et al, 2008;Mohamed et al, 2014;Risso et al, 2010). According to Ahmed et al (2019), increased reaction velocities are observed probably due to the configurational modifications on enzyme after interacting with the matrix and molecular flocking caused by immobilization.…”
Section: Kinetic Parametersmentioning
confidence: 98%
“…The increase in K m after immobilization was probably due to the mass transfer resistance to the substrate into the polymer matrix, and effect of the increasing degree of polymerization of substrate caused increase in this value (Abdel-Naby et al, 1999;Curcio et al, 2014;Kusano et al, 1989;Mazutti et al, 2007). Higher V max observed for the immobilized enzyme was rather unusual; however, such increase has been observed in case of immobilized inulinase (Calixto-Romo et al, 2008;Mohamed et al, 2014;Risso et al, 2010). According to Ahmed et al (2019), increased reaction velocities are observed probably due to the configurational modifications on enzyme after interacting with the matrix and molecular flocking caused by immobilization.…”
Section: Kinetic Parametersmentioning
confidence: 98%
“…Typically, immobilized enzymes have lower V max values than their free counterparts [37], and this phenomenon is associated with conformational changes of the enzyme during immobilization [18]. Higher V max values after immobilization have been reported for inulinase [38], invertase [39], and β -galactosidase [40]. However, this is an unusual behavior and the mechanistic basis for this positive feature requires further investigation [37].…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of DE, mDE, and mDE-APTES consist of the remarkable peaks for asymmetric stretching vibration of Si-O-Si (1090 cm -1 ), symmetric stretching vibration of Si-O (798 cm -1 ), and bending vibration of Si-O-Si (468 cm -1 ) (Fig. 1b) (de los Ángeles Calixto-Romo et al 2008;Janićijević et al 2015). The band of 3600 cm -1 is also due to stretching vibration frequency of SiO-H.…”
Section: Ftir Spectra Of the Supportmentioning
confidence: 99%